Pest Control on Shallots Using Solar-Powered Trap Lights in Srimulyo Village, Sragen Regency - Hendri Widiyandari; Yofentina Iriani; Kusumandari Kusumandari; Fahru Nurosyid; Khairuddin Khairuddin; Risa Suryana (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Shallots one of a leading vegetable commodity in Central Java. However, the shallot farming industry is frequently confronted with the issue of decreasing yields due to the presence of plant pests. Onion plant pests include the butterfly (Spodoptera exigua) and the leafminer fly (liriomyza). There are two approaches to dealing with this pest problem: pesticides/insecticides and light traps. In terms of organic farming methods, the use of light traps is more profitable. However, the operational costs are quite high because farmers must have a generator to generate electricity, diesel fuel to turn on the generator, oil to lubricate the engine, operators, or must connect to the PLN electricity network. So, we used a solar-powered pest trap lamp system with Li-ion batteries as the energy storage medium to solve this problem. In Srimulyo village, Gondang district, Sragen regency, community service activities such as installing pest trap lights to control pests on shallots were carried out. The onion farmer group association is the service activity's partner (Gapoktan). This activity was well received by shallot farmers because the presence of this light trap can reduce pest attacks.